Do campo para sala de aula: experiências matemáticas em um assentamento rural no Oeste maranhense - SILVA, Filardes de Jesus Freitas da (Universidade Federal do Pará, 2017)
Nowadays the expression Countryside Education managed to establish itself as a concept related to a specific model of education. Much more than a practice, it is about an analysis category, not only due to education, but primarily because of the historicity of sociocultural practices which happen in countryside communities. And the school inserted in this context has to be in constant dialogue with the protagonist subjects in this scenario. In this perspective, Ethnomathematics arises as an important research field and tendency in Mathematical Education, whose outlook is investigative about the theme. In Brzil, according to INCRA dates, there are 9,290 settlements which assist approximately 969,640 families. According to these data, the state of Maranhão appears in second place in the number of settlements, being 1025 with 131,630 assisted families, only second to the state of Pará, with 1055 settlements The present work aims to study the search for dialogue between the know-hows that emerge from the social practices of the workers in a countryside settlement in the west of the state of Maranhão and the knowledge spread by the official curriculum of the schools. The main theoretical contributions that guided the study were D’Ambrosio (2012, 2011, 2001, 1998, 1986), Freire(2014), Mendes (2010, 2015) and Radford (2011, 2014). The research subjects are four people from the settlements and four teachers who teach mathematics at the settlement school. The investigation presents itself as an action-research, of a qualitative approach; however, in its architecture the study seeks to reconciliate some ethnographic techniques, such as the direct and participant observation, the field diary, life history and interviews. Starting from the organization and analysis of the information obtained in the field research and its connections to the theoretical contributions which served as basis for the construction of the thesis it was possible to organize a pedagogical proposal to the teaching of mathematics in countryside settlement schools based on the identified sociocultural practices, and mainly centered on the generating themes and questions that appeared in loco.